2017
DOI: 10.1007/s10290-017-0293-1
|View full text |Cite|
|
Sign up to set email alerts
|

Trade liberalization and the wage gap: the role of vertical linkages and fixed costs

Abstract: This paper studies the labor market impacts of trade liberalization, and specifically tariff reductions, with a focus on the wage gap between skilled and unskilled workers in presence of vertical linkages in the fixed costs of production. To that purpose, we develop and empirically test a monopolistic competition model with variable elasticity of substitution and labor differentiated by skill level, where skilled workers are the residual claimants of savings on imported inputs. Consistently with the model pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Our preferred speci cation is column 4 because its ability to capture endogenous variables. Previous studies have highlighted the strengths of this estimation (see Amiti & Cameron, 2012;Di Comite., Nocco, & Ore ce, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Our preferred speci cation is column 4 because its ability to capture endogenous variables. Previous studies have highlighted the strengths of this estimation (see Amiti & Cameron, 2012;Di Comite., Nocco, & Ore ce, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, the gap widened (Davis and Mishra, 2007;Goldberg and Pavcnik, 2007). Earlier explanations of the wage premium's persistence emphasised friction in the labour 2 See for example, Revenga (1997), Hanson andHarrison (1999), Feliciano (2001), Attanasia et al (2004), Currie and Harrison (1997), Topalova (2004), Robertson (2000Robertson ( , 2004 and Wacziarg and Wallack (2004); Amiti and Konings (2007); Topalova and Khandelwal (2011);Di Comite et al (2018); Lechthaler and Mileva (2019); Hahn and Choi (2022).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…8 Structural changes in the labor market after trade liberalization not only decreases fixed costs of production but also increases the productivity of goods, which leads to increased wage premiums for skilled labor relative to unskilled labor due to the increase in profits (Arbache et al, 2004;Comite et al, 2018). Many studies have also shown that a reduction in trade barriers increases the relative demand for skilled labor by reallocating factors toward more skillintensive firms (Burstein and Vogel, 2017;Feenstra and Hanson, 1997).…”
Section: _________________________mentioning
confidence: 99%